Proceedings of the 4th International Symposium on Memory Management 2004
DOI: 10.1145/1029873.1029892
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic object sampling for pretenuring

Abstract: Many state-of-the-art garbage collectors are generational, collecting the young nursery objects more frequently than old objects. These collectors perform well because young objects tend to die at a higher rate than old ones. However, these collectors do not examine object lifetimes with respect to any particular program or allocation site. This paper introduces low-cost object sampling to dynamically determine lifetimes. The sampler marks an object and records its allocation site every n bytes of allocation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…[26][27][28][29]). Hirzel et al studied a suite of benchmarks and concluded that object connectivity correlates strongly with object lifetime [30].…”
Section: Profilingmentioning
confidence: 99%
“…[26][27][28][29]). Hirzel et al studied a suite of benchmarks and concluded that object connectivity correlates strongly with object lifetime [30].…”
Section: Profilingmentioning
confidence: 99%
“…In [27], sampling is used to characterize object allocation behavior while we use it to track and estimate sharing profile. In our system, space constraint is much tighter since we cannot store or transfer too much sampling result.…”
Section: ) Accuracymentioning
confidence: 99%
“…Thus, we have to start with a wide sampling gap (actually 4KB) and dynamically adjust it only when accuracy is not enough. In contrast, a much smaller sampling gap (256B) is chosen and fixed in [27].…”
Section: ) Accuracymentioning
confidence: 99%
“…If an object escapes into the sink, the object is considered long-lived. Then, it is possible to avoid the processing of the long-lived object by copying it out of the frequently collected region similarly to the pretenuring studies [5], [7].…”
Section: Phase Identificationmentioning
confidence: 99%
“…However, several studies [1]- [5] show that accurately predicting object lifetimes is difficult to achieve. The prediction mechanisms in those works either fail to attain performance improvement or are not applicable to various applications.…”
Section: Introductionmentioning
confidence: 99%